Functionalised microscale nanoband edge electrode (MNEE) arrays: the systematic quantitative study of hydrogels grown on nanoelectrode biosensor arrays for enhanced sensing in biological media. (13th August 2018) - Piper, Andrew; Alston, Ben M.; Adams, Dave J.; Mount, Andrew R.
Abstract : We demonstrate a hydrogel-coated nanoelectrode array biosensor that is resistant to biofouling. Abstract : Nanoelectrodes and nanoelectrode arrays show enhanced diffusion and greater faradaic current densities and signal-to-noise ratios compared to macro and microelectrodes, which can lead to enhanced sensing and detection. One example is the microsquare nanoband edge electrode (MNEE) array system, readily formed through microfabrication and whose quantitative response has been established electroanalytically. Hydrogels have been shown to have applications in drug delivery, tissue engineering, and anti-biofouling; some also have the ability to be grown electrochemically. Here, we combine these two emerging technologies to demonstrate the principles of a hydrogel-coated nanoelectrode array biosensor that is resistant to biofouling. We first electrochemically grow and analyze hydrogels on MNEE arrays. The structure of these gels is shown by imaging to be electrochemically controllable, reproducible and structurally hierarchical. This structure is determined by the MNEE array diffusion fields, consistent with the established hydrogel formation reaction, and varies in structural scale from nano (early time, near electrode growth) to micro (for isolated elements in the array) to macro (when there is array overlap) with distance from the electrode, forming a hydrogel mesh of increasing density on progression from solution to electrode. There is also increased hydrogel structural density observed at electrode corners, attributable to enhanced diffusion. The resulting hydrogel structure can be formed on (and is firmly anchored to/through) an established clinically relevant biosensing layer without compromising detection. It is also shown to be capable, through proof-of-principle model protein studies using bovine serum albumin (BSA), of preventing protein biofouling whilst enabling smaller molecules such as DNA to pass through the hydrogel matrix and be sensed. Together, this demonstrates a method for developing reproducible, quantitative electrochemical nanoelectrode biosensors able to sense selectively in real-world sample matrices through the tuning of their interfacial properties.